Gestational trophoblastic neoplasia after spontaneous human chorionic gonadotropin normalization following molar pregnancy evacuation - Braga, Antonio; Maesta, Izildinha [UNESP]; Matos, Michelle; Elias, Kevin M.; Rizzo, Julianna; Campos Viggiano, Mauricio Guilherme (Elsevier B.V., 2015)
Objective. To evaluate the risk of gestational trophoblastic neoplasia (GTN) after spontaneous human chorionic gonadotropin normalization in postmolar follow-up. Methods. Retrospective chart review of 2284 consecutive cases of hydatidiform mole with spontaneous normalization of hCG following uterine evacuation treated at one of five Brazilian reference centers from January 2002 to June 2013. Results. After hCG normalization, GTN occurred in 10/2284 patients (0.4%; 95% CI 0.2%4.8%). GTN developed in 9/1424 patients (0.6%; 95% Cl 03%-1.2%) after a complete hydatidiform mole, in 1/849 patients (0.1%; 95% CI < 0.01%-0.7%) after a partial hydatidiform mole, and in 0/13 patients (0%; 95% CI 0%-27%) after a twin molar pregnancy. The median time to GTN diagnosis after hCG normalization was 18 months, and no diagnoses were made before six months of postmolar surveillance. Patients who required more than 56 days to achieve a normal hCG value had a ten-fold increased risk of developing GTN after hCG normalization (9/1074; 0.8%; 95% CI 0.4%-1.6%) compared to those who reached a normal hCG level in fewer than 56 days (1/1210;0.08%; 95% Cl < 0.01%-0.5%; p = 0.008). All patients presented with symptoms at the time of GTN diagnosis. Conclusion. GIN after spontaneous hCG normalization following molar pregnancy is exceedingly rare, and the few patients who do develop GTN after achieving a normal hCG value are likely to be diagnosed after completing the commonly recommended six months of postmolar surveillance. Current recommendations for surveillance after hCG normalization should be revisited. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Gestational trophoblastic disease; Human chorionic gonadotropin; Molar pregnancy; Gestational trophoblastic neoplasia; Recrudescent disease